2021
DOI: 10.14202/vetworld.2021.329-338
|View full text |Cite
|
Sign up to set email alerts
|

The deleterious effect of postpartum pyometra on the reproductive indices, the metabolic profile, and oxidant/antioxidant parameters of dairy cows

Abstract: Background and Aim: Postpartum uterine infectious diseases, such as pyometra, have discrepancy with both health and, subsequently, productivity of dairy cows due to its high prevalence and the high cost of treatment. Therefore, this study investigates the influence of pyometra on the reproductive indices, the metabolic profile, and oxidant/antioxidant parameters of the pyometric animal compared to those of healthy ones. Materials and Methods: The study included 30 cows. The animals were differentiated into tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…imals(El-Deeb et al, 2019;El-Deeb & Buczinski, 2015;El-Deeb & Elmoslemany, 2015) Amin et al (2021). found that serum MDA levels were significantly higher in cows with pyometra compared to healthy cows.…”
mentioning
confidence: 97%
“…imals(El-Deeb et al, 2019;El-Deeb & Buczinski, 2015;El-Deeb & Elmoslemany, 2015) Amin et al (2021). found that serum MDA levels were significantly higher in cows with pyometra compared to healthy cows.…”
mentioning
confidence: 97%
“…In the present study, TAC significantly decreased in pyometra cases coincident with a decrease in SOD and CAT activities and an increase in NO and MDA levels. Former studies indicated a decrease in serum TAC levels (Amin et al, 2021) in pyometric dairy cows, and SOD and catalase in pyometric bitches (Rautela et al, 2018), perhaps due to an exhaustion of antioxidant system (Amin et al, 2021). SOD is considered as the 1st line of defense against ROS where it removes both intra-and extracellular superoxide radicals and decreases the danger of these radicals (Grieve and Shah, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Data regarding the changes in biochemical and hormonal parameters in bitches and queens showed pyometra is presented in table (2). There was significant increase in CRP (P< 0.01, 0.05), NO (P< 0.05), MDA (P< 0.01, 0.005), P4 (P< 0.05, 0.0001), but a decrease in SOD (P<0.0005, 0.005), CAT (P<0.05), TAC (P<0.05), in pyometric bitch and queen, respectively.…”
Section: Oxidative Stress and Hormonal Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…The non-specific bacteria most commonly involved were Escherichia coli, Staphylococcus, Streptococcus, Corynebacterium, Bacillus, Pseudomonas, Micrococcus and Klebsiella (Bhat et al, 2014). The problems that arised due to non-specific bacterial infections in the reproductive tract were a decrease in the calving rate, decreased body weight, and the occurrence of repeat breeding, pyometra (chronic endometritis), and infertility, resulting in declined reproductive efficiency (Amin et al, 2021). The results of the study of Sharma et al (2009) showed that there were E. coli and S. aureus bacteria from the cervical mucus of repeat breeder cows.…”
Section: Introductionmentioning
confidence: 99%